USP8‐Dependent Family Tyrosine Kinase Promotes the Malignant Progression of Esophageal Squamous Cell Carcinoma by Upregulating Protein Tyrosine Kinase 2 Expression - Yuechang Wu; Dubiao Xian; Yunzhong Liu; Ding Huang; Qingfeng Liu; Shubo Yang (Thoracic Cancer)
ABSTRACT Background Esophageal squamous cell carcinoma (ESCC) is a lethal malignancy, and the molecular underpinnings of its aggressive behavior are not fully understood. FYN proto‐oncogene, Src family tyrosine kinase (FYN) has been linked to cancer progression, yet its role in ESCC remains elusive. This study investigated the influence of FYN on ESCC malignancy. Methods Quantitative real‐time polymerase chain reaction was used to assess the mRNA expression of FYN, while western blotting and immunohistochemistry (IHC) assays were performed to detect the protein expression of FYN, ubiquitin specific peptidase 8 (USP8) and protein tyrosine kinase 2 (PTK2). Cell viability was measured with a cell counting kit‐8 assay, and cell apoptosis was evaluated using flow cytometry. Results FYN expression was increased in ESCC tissues and cells when compared with normal esophageal tissues and normal esophageal epithelial cells. Knockdown of FYN inhibited cell invasion, migration, stem‐like traits, and glycolysis, while promoting apoptosis. USP8 was shown to stabilize FYN protein expression through its deubiquitinating activity in ESCC cells. Overexpression of FYN reversed the effects of USP8 silencing on the malignant phenotypes of ESCC cells in vitro and in vivo. FYN upregulated PTK2 expression in both TE1 and KYSE150 cell lines. Furthermore, PTK2 overexpression reversed the effects of FYN silencing on the malignant phenotypes of ESCC cells. Further, USP8 silencing‐induced inhibitory effect on PTK2 protein expression was counteracted after FYN overexpression. Conclusion USP8‐dependent FYN contributed to the malignant progression of ESCC by interacting with PTK2. Targeting this pathway may offer a novel therapeutic strategy for ESCC treatment.